THE COVID-19 LOCKDOWN EFFECTS ON MENTAL WELL-BEING AND RELIGIOSITY: EVIDENCE FROM INDONESIA - Andariesta, Dinda Thalia; Ridhwan, Masagus M.; Rezki, Jahen Fachrul; Indira, Mutiara Helga (Journal of Islamic Monetary Economics and Finance, 2023)
We investigate the effects of COVID-19 lockdowns on frequency of online search on mental well-being and religiosity-related terms in Indonesia using high-frequency data from Google Trends and Bank Indonesia Consumer Survey from January 1st, 2018, to February 28th, 2021. Monthly search terms and consumer survey data are merged at the provincial level, which results in a total of 131,300 individual observations. Using event analysis and instrumental variable approaches, our study suggests that lockdown policy is significantly associated with higher search intensity of mental well-being and religiosity-related terms compared to the pre-lockdown period. Our findings suggest that mentally disturbed people tend to lean on religion to cope with stressful events during a crisis. Our study has substantial policy implications on ensuring appropriate government interventions that minimize the detrimental effect of COVID-19 on mental well-being. Acknowledgment We are grateful to Bank Indonesia's Department of Statistics for helping us to provide the survey data.